Hosts, parasites and environment: the particular case of domestic and wild ungulates of central Portugal - Oliveira, Lucia da Silva Soares (2016)
The helminthosis affecting ruminants represent a major constraint to livestock production globally. Since livestock plays a central role in the sustainability of local rural economy and in the livelihood of their populations, the implementation of an adequate health management is vital. This is only possible through surveillance of the resident parasites at a regional scale. The focus of this work are domestic ruminants, namely cattle (Bos taurus), goats (Capra hircus) and sheep (Ovis aries), due to its economic and social relevance in the study area, Montemuro, Arada and Freita mountains. Between November 2014 and August 2015, 96 faecal samples were collected randomly in several counties. To determine the presence of helminths, were performed some coprological techniques that allow us to identify gastrointestinal nematodes eggs (Nematodirus spp., Strongyloides papillosus, Trichuris ovis and gastrointestinal strongyles), L1 larvae of pulmonary nematodes (Dictyocaulus viviparus, Muellerius capillaris and Protostrongylus spp.), tapeworms eggs (Moniezia benedeni) and eggs of liver fluke Fascicola hepatica. Nematoda was the most prevalent class (n=70; 72,9%) in the hosts under study. Within this class, gastrointestinal strongyles predominated both in cattle (n=20; 52,6%) and in small ruminants (n=44; 75,9%). The only species of trematode found was Fasciola hepatica, a zoonotic parasite, which was only observed in the warmer months. Mixed infections were constant throughout the year, showing a gradual increase, with 78% of prevalence in small ruminants and 55% in cattle. Strongyles were observed throughout the year, with a higher prevalence in May-July, after a particularly rainy month, coinciding with an increase in temperature and low rainfall and relative humidity. L1 larvae of pulmonary nematodes, of small ruminants, was also present throughout the year, coinciding the increased of its prevalence with months of low temperatures and rainfall, between January and March. The results obtained in the faecal egg count method (FEC) coincide with the qualitative methods: the highest burdens were seen in the warmer months, where all hosts showed high infection levels, contrary to annual norm. Additionally, a literature review was also done, addressing the role of parasites at community level, based on the cross-transmission of helminths among domestic and wild ruminants. This allowed to conclude that nematodes, for its general and ubiquitous character, exhibit the most common parasites of wild and domestic ruminants. One can infer that the study area is prone to transmission between different species given that some of the found parasites are referred as interspecific parasites. This study demonstrates the importance of background and control of parasitic infections in domestic-wild interface, requiring a multi-disciplinary team of biologists, veterinarians, human doctors and livestock farmers in order to prevent possible epidemics affecting not only domestic ruminants, but also wild ones and the human being.